VEGETATIVE PROPAGATION AND ESTABLISHMENT OF LYCIUM CHINENSE MILL. AND LYCIUM BARBARUM L. PLANTATIONS IN NAMANGAN REGION - Alikarieva Durdona Mirmakhmudovna; Merganov Avazkhon Turgunovich (Bright Mind Publishing, 2025)
This article presents the results of research on vegetative propagation and the establishment of industrial plantations of Lycium chinense Mill. and Lycium barbarum L. in the Namangan region. Green semi-woody cuttings treated with growth stimulants (Epin, Kornevin, IAA, IBA) were planted in a film greenhouse with artificial fog. The rooting period, rooting percentage, and optimal conditions for harvesting and planting cuttings were determined. The obtained results allow developing recommendations for the rational organization of plantations for industrial cultivation of Lycium.
Keywords: Lycium chinense Mill., Lycium barbarum L., vegetative propagation, rooting, green cuttings, growth stimulants, mist greenhouse, industrial plantation.